Exploring the Impact of Massive Open Online Courses (MOOCs) on Higher Education in Afghanistan: Opportunities, Challenges, and Policy Implications - Azimi, Irfanullah; Ebrahemi, Mosa; Merzaee, Mohammad Jawad (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Massive Open Online Courses or MOOCs have emerged as a potential solution to enhance access to education globally, including in countries with limited resources such as Afghanistan. This study explores the integration of Massive Open Online Courses in Afghanistan's higher education system through qualitative analysis. Data were gathered from students and faculty across multiple Afghan universities to uncover key themes and implications associated with MOOC integration. The analysis revealed a diverse demographic composition among respondents, with a concentration of younger participants. A total of One hundred twenty participants, including eighty students and forty faculty members, contributed to the study. Perceptions regarding MOOC interventions were predominantly positive, highlighting their potential to enhance educational experiences. However, challenges such as task complexity and the digital divide underscored the need for tailored strategies to address contextual constraints. Despite obstacles, interventions were perceived to positively impact motivation levels and educational outcomes. In conclusion, the study advocates for a nuanced approach to MOOC implementation, considering regional disparities and population dynamics. By contextualizing MOOC integration within Afghanistan's socio-economic and technological landscape, stakeholders can develop targeted interventions to maximize benefits and mitigate challenges. These insights contribute to the broader discourse on leveraging digital technologies for educational advancement, offering practical implications for enhancing access and quality in higher education settings.